2006
DOI: 10.1130/b26351.1
|View full text |Cite
|
Sign up to set email alerts
|

Age, provenance, and tectonic setting of Paleoproterozoic quartzite successions in the southwestern United States

Abstract: New fi eld studies combined with U-Pb zircon geochronology constrain the ages of deposition and sedimentary provenance of Paleoproterozoic quartzite successions exposed in the southwestern United States. Orthoquartzites were deposited in shortlived basins at two times (ca. 1.70 and 1.65 Ga) during crustal assembly of southern Laurentia. The more voluminous ca. 1.70 Ga successions occur in southern Colorado, northern New Mexico, and central Arizona and are interpreted here to be time correlative, though not nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(104 citation statements)
references
References 67 publications
4
99
1
Order By: Relevance
“…Han et al, 2015). Many different methods have been applied to determine the maximum depositional age of strata using U-Pb ages of detrital zircons (Dickinson and Gehrels, 2009;Jones et al, 2009). Dickinson and Gehrels (2009) concluded that the weighted mean ages of youngest cluster of two or more grain ages (n ≥ 2) overlapping in age at 1σ (YC1σ [2+]) are more consistently compatible with depositional ages, especially for strata derived from contemporaneous volcanic rocks.…”
Section: Constraint On Depositional Agesmentioning
confidence: 99%
“…Han et al, 2015). Many different methods have been applied to determine the maximum depositional age of strata using U-Pb ages of detrital zircons (Dickinson and Gehrels, 2009;Jones et al, 2009). Dickinson and Gehrels (2009) concluded that the weighted mean ages of youngest cluster of two or more grain ages (n ≥ 2) overlapping in age at 1σ (YC1σ [2+]) are more consistently compatible with depositional ages, especially for strata derived from contemporaneous volcanic rocks.…”
Section: Constraint On Depositional Agesmentioning
confidence: 99%
“…; thus, less mature sediments would have been expected. Such an apparent contradiction was already observed and described by Jones et al (2009) for the Paleoproterozoic orthoquartzitic Yavapai and Matzatal successions along the southern Laurentian margin. As stated earlier, these can be compared to the Västervik succession as all were deposited along the long-lived southern margin of the combined Laurentia-Baltica craton in similar geodynamic settings.…”
Section: Age and Homogeneity Of The Deposited Materialsmentioning
confidence: 79%
“…Buchan et al 2000) can be followed from SE-Sweden (Svecofennian metaarenites) via Greenland (Ketilidian metapsammites) to the SW-United States (Yavapai and Matzatal orthoquartzites) along a more than 9,000 km long continental margin (Beunk and Page 2001;Karlstrom et al 2001). Deposition ages of the sedimentary successions show a general trend with younging ages from Baltica (1.86-1.83 Ga; Bergman et al 2008) to Ga; Garde et al 2002) and finally Laurentia (1.70-1.65 Ga;Jones et al 2009). Deposition environments are generally described as being shallowwater fluvial with marine and tidal influences (Jones et al 2009;Sultan and Plink-Björklund 2006;Garde et al 2002).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations